A Quantitative Study of Speaking Strategies, Anxiety, Motivation, and Attitudes among Chinese Non-English-Major Undergraduates in English Language Learning - Wenxin, Lu (Universiti Malaysia Sarawak, 2026)
English proficiency is crucial for university students in China, given the country's emphasis on English education. As globalization and China's international involvement increase, English is vital for academic success, career growth and cross-cultural communication. The government and institutions have made it a core subject and a key requirement for university entrance and graduation. Nevertheless, many Non-English-Major undergraduates encounter difficulties in speaking English, largely due to factors such as language anxiety, low motivation and the use of ineffective or limited speaking strategies. Clarifying how these strategies and emotional factors interact to influence learners' motivation and attitudes is essential for improving English language education. While existing research has explored these relationships, findings remain inconclusive. This study aims to assess the levels and interrelationships of speaking strategies, speaking anxiety, learning motivation and learning attitudes among Chinese undergraduates studying English as a foreign language (EFL). Additionally, it investigates the relationships among these variables. A quantitative research method was employed, utilizing purposive sampling to collect data from the target population. Data were analysed using descriptive statistics to summarize the data, correlation analysis to explore associations between key variables, and regression analysis to examine the relationships between variables, all conducted using SPSS version 27.0. The study surveyed first- and second-year Non-English-Major students from six universities in Jinan, Shandong Province, China. A total of 500 questionnaires were distributed, yielding 415 valid responses and an 83% response rate. The sample comprised 203 male and 212 female students. The findings indicate that among various speaking strategies, "Message Abandonment Strategies" were the most frequently employed. Regarding speaking anxiety, students reported the highest levels of anxiety related to "Test Anxiety." In terms of learning motivation, "Extrinsic Motivation - Social" emerged as the most prominent factor, while "Cognitive Attitude" was the strongest component of learning attitudes. Grounded in theoretical frameworks of Socio-Educational Model, this study proposed hypotheses regarding the relationships among the investigated variables. The results demonstrated that both speaking strategies and speaking anxiety were significantly related to learning motivation, which, in turn, was positively associated with learning attitudes. These findings underscore the pivotal role of learning motivation in shaping students' attitudes toward English learning. Based on these insights, educators and policymakers should prioritize strategies aimed at reducing speaking anxiety and promoting effective speaking strategies to enhance students’ motivation. This study contributes to the ongoing discourse on English language education by providing empirical evidence to inform pedagogical practices for Non-English-Major undergraduates in China.